Analysis of Micro Small Enterprises (MSEs) Customer Satisfaction in a Global Context Studies on Shoraya Batik Indonesia - Fadali Rahman; Imam Mukhlis; F. Danardana Murwani; Achmad Ali Said (International Journal of Scientific Multidisciplinary Research, 2023)
Customer satisfaction is a measure that determines how well a company's product or service meets customer expectations. This study aims to analyze customer satisfaction MSEs in the context of a global study on Indonesian Batik Shoraya. The research was conducted using a qualitative approach and data collection techniques through in-depth interviews with 10 Shoraya Batik customers, 5 domestic and 5 international. The results showed that customer satisfaction with Shoaraya Batik Indonesia products was influenced by service quality, product quality, price, emotional factors, cost and convenience. Customers expect fast and responsive service, quality and reliable products, affordable prices, and positive emotional experiences with the Shoaraya Batik Indonesia brand. Cost and ease of transaction are also important factors influencing customer satisfaction. In a global context, Shoaraya Batik Indonesia's customers have high expectations for products that can compete with international brands. Customers expect Shoraya Batik Indonesia to maintain consistent product and service quality, as well as develop innovative products that are in line with global trends. Even though Shoaraya Batik Indonesia already has a loyal customer base in Indonesia, the challenge it faces in entering the global market is competition from established international brands. Based on the results of this study, it is suggested that Shoraya Batik Indonesia continue to improve service and product quality and maintain affordable and competitive prices